Changes in Anterior and Posterior Corneal Elevation in Patients With Allergic Conjunctivitis - Wang, Qian; Yu, Fei; Feng, Ziqing; Li, Weihua; Li, Naiyang; Du, Xinyue; Zhao, Xuan; Li, Saiqun; Yuan, Jin (Frontiers in Medicine, 2021)
Purpose: To evaluate corneal elevation changes in patients with allergic conjunctivitis (AC) and to analyze their correlations with ocular allergy signs and corneal biomechanical alterations. Methods: Thirty patients (30 eyes) with AC and twenty normal subjects (20 eyes) were included in this prospective study. All participants underwent a complete ocular examination, including corneal tomography by Pentacam and corneal biomechanics evaluation by Corvis ST. AC patients were evaluated for their eye rubbing frequency and ocular allergic signs. Results: The elevation at the thinnest location (TE) and the central location (CE), the elevation difference at the thinnest location (TED) and the central location (CED), and the mean value of elevation difference in the central 4 mm zoom (MED) of both the anterior and posterior corneal surface were significantly higher in the AC group than in the normal group (p<0.05 for all). In AC patients, only anterior corneal elevation parameters were positively correlated with eye rubbing frequency and ocular allergy sign severity (p<0.05 for all), while the tomography and biomechanical index (TBI) was positively correlated with the elevation parameters of both the anterior and posterior corneal surfaces (p<0.05 for all). Conclusions: AC patients carry an increased risk of corneal ectasia. Posterior corneal elevation parameters are sensitive and reliable predictors of keratoconus (KC) risk in AC patients.